2020
DOI: 10.1088/2053-1583/ab6f79
|View full text |Cite
|
Sign up to set email alerts
|

Influence of channel thickness on charge transport behavior of multi-layer indium selenide (InSe) field-effect transistors

Abstract: Atomically thin Van der Waals solids that exhibit direct band gap in their few layer form can substantially impact the field of two dimensional (2D) materials based electronic devices and related applications. Here we report on electronic charge transport behavior of multi layer ntype InSe field-effect transistor (FET) devices fabricated on SiO 2 /Si substrate with seven different channel thicknesses, t > 20 nm, well within its direct band gap regime. Through gate dependent conductivity measurements over a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 57 publications
(84 reference statements)
2
9
0
Order By: Relevance
“…Detailed analysis and mechanisms of electronic transport in these devices are mentioned elsewhere [20]. Room temperature transfer characteristics curve is shown in Figure 2(d).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Detailed analysis and mechanisms of electronic transport in these devices are mentioned elsewhere [20]. Room temperature transfer characteristics curve is shown in Figure 2(d).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned earlier, layer thickness plays an important role in electrical/opto-electronic transport properties of 2D Van der Waals materials. It has been shown that mobility varies as thickness changes [20,34]. Also, the underlying substrate plays an import role in opto-electronic transport as charge traps states are primarily originate from underlying substrate [18,35].…”
Section: 𝑅 = 𝐼 𝑝ℎ𝑜𝑡𝑜 𝑃 𝑖𝑛mentioning
confidence: 99%
See 2 more Smart Citations
“…The detail device fabrication method and electrical transport characterization are presented in one of our previous publications [22,23]. In short the devices were fabricated on Silicon/Silicon dioxide (SiO 2 ) wafers with a (SiO 2 ) thickness of 1000 nm.…”
Section: Device Fabricationmentioning
confidence: 99%